The Effectiveness of Project –Based Learning in the Acquisition of English as a Foreign Language - Supe, Olga; Kaupuzs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the last years the project – based learning has become a popular teaching method in Latvia. Project work is a student-centred teaching approach; it motivates students to use language in real life situations and involves a great number of students’ feelings, talents, skills and knowledge in the education process. It is a way to express students’ own decisions, experience, almost dreams. This approach can be used for both: small kids (beginners’ level) and for adolescents (upper-intermediate level).The goal of this research is to analyse the effectiveness of project –based learning in the acquisition of English as a foreign language This investigation is based upon Legutke, Thomas, Fried-Booth, Haines, researches.